Serving diverse students in Canadian higher education - Cox, Donna Gail Hardy, 1961-; Strange, Charles Carney (McGill-Queen's University Press, 2016)
"In recent decades, the Canadian post-secondary education system has evolved to become more inclusive, now welcoming groups historically excluded from its many opportunities. Inviting the reader to explore the consequences of a rapidly changing student population, Serving Diverse Students in Canadian Higher Education presents new thinking about how education in general, and student services in particular, should be designed and delivered. A follow-up to Donna Hardy Cox and C. Carney Strange's Achieving Student Success (2010), this volume focuses on best programs and practices in Canadian colleges and universities to improve the educational experiences of students who are Indigenous, people of colour, Francophone, LGBTQQ, disabled, and adult learners, as well as international and first-generation students. Presenting findings obtained from both personal insight and relevant research, higher education practitioners and scholars from across the country detail the characteristics, concerns, and specific needsof each diverse group, to conclude that the success of these new students and the future of Canadian society depends on its post-secondary institutions' capacities to acknowledge students' differences, capitalize on their gifts, and accommodate them accordingly."--